Early Diagnosis Of Children With Speech Disorders And Provision Of Primary Consultative Support Through The Use Of Information And Communication Technologies (Journal of Pedagogical Inventions and Practices, 2025)
This study explores the role of information and communication technologies (ICT) in the early diagnosis of children with speech disorders and the provision of primary consultative support. The research emphasizes the importance of timely identification of speech impairments, the integration of digital tools for diagnostic assessment, and the development of consultative frameworks that assist both specialists and parents. By leveraging modern ICT solutions, the process of early intervention becomes more effective, accessible, and systematic, ultimately contributing to improved outcomes in special pedagogy and speech therapy